Preoperative Use of Intravenous Contrast Media Is Associated With Decreased Excellent Response Rates in Intermediate-Risk DTC Patients Who Subsequently Receive Total Thyroidectomy and Low-Dose RAI Therapy - Lan, Wei; Renjie, Wang; Qichang, Wan; Feiyue, Teng; Qingjie, Ma; Bin, Ji (Frontiers in Oncology, 2020)
Purpose: To evaluate the impact of preoperative use of intravenous contrast media (ICM) on the excellent response (ER) rates in a cohort of intermediate risk differentiated thyroid cancer (DTC) patients who received total thyroidectomy (TT) and low-dose radioactive iodine (RAI) therapy. Methods: A total of 683 consecutive patients were retrospectively reviewed in a single center between August 2016 and August 2018. Patients were divided into ICM group (n=532) and non-ICM group (n=151). ICM patients were 1:1 propensity matched to non-ICM patients based on T stage, N stage and urinary iodine. Risk adjusted logistic regression models were constructed to assess the association between the use of ICM and ER rates. Results: ICM patients had significantly higher T stage (P<0.001), N stage (P<0.001), urinary iodine (P<0.001) and ps-Tg (P=0.042) than non-ICM patients. Preoperative use of ICM was found to be significantly associated with decreased ER rates in both the primary cohort (OR 0.47, 95% CI 0.32-0.71, P<0.001) and the matched cohort (OR 0.48, 95% CI 0.25-0.94, P=0.031). Subgroup analysis on RAI delay time in the primary cohort revealed that ER rates in ICM patients were significantly lower than that of non-ICM patients for 1-2 months (P=0.0245) and >2-3 months (P=0.0221) subgroups, but not for >3-4 months, >4-5 months and >5-6 months subgroups (All P＞0.05). A delay time of >3-4 months exhibited the highest ER rate (63.08%) within the ICM group. Conclusions: Preoperative use of ICM is associated with decreased ER rates in intermediate risk DTC patients who subsequently receive TT and low-dose RAI therapy. For such patients, if ICM has already been received, a RAI delay time of >3-4 months would seem to be more appropriate to achieve better ER rates.